Populations of latent Mycobacterium tuberculosis lack a cell wall: Isolation, visualization, and whole-genome characterization. Issue 1 (March 2016) - Velayati, Ali Akbar; Abeel, Thomas; Shea, Terrance; Konstantinovich Zhavnerko, Gennady; Birren, Bruce; Cassell, Gail H.; Earl, Ashlee M.; Hoffner, Sven; Farnia, Parissa
Abstract: Objective/Background: Mycobacterium tuberculosis (MTB) causes active tuberculosis (TB) in only a small percentage of infected people. In most cases, the infection is clinically latent, where bacilli can persist in human hosts for years without causing disease. Surprisingly, the biology of such persister cells is largely unknown. This study describes the isolation, identification, and whole-genome sequencing (WGS) of latent TB bacilli after 782 days (26 months) of latency (the ability of MTB bacilli to lie persistent). Methods: The in vitro double-stress model of latency (oxygen and nutrition) was designed for MTB culture. After 26 months of latency, MTB cells that persisted were isolated and investigated under light and atomic force microscopy. Spoligotyping and WGS were performed to verify the identity of the strain. Results: We established a culture medium in which MTB bacilli arrest their growth, reduce their size (0.3–0.1 μm), lose their acid fastness (85–90%) and change their shape. Spoligopatterns of latent cells were identical to original H37 Rv, with differences observed at spacers two and 14. WGS revealed only a few genetic changes relative to the already published H37 Rv reference genome. Among these was a large 2064-bp insertion (RvD6), which was originally detected in both H37 Ra and CDC1551, but not H37 Rv . Conclusion: Here, we show cell-wall free cells of MTB bacilli in their latent state, and the biological adaptation of these cells was more phenotypic in nature than genomic. These cell-wall free cells represent a good model for understanding the nature of TB latency.